Origem de aferências monoaminérgicas e CART-érgicas ao circuito elementar do reflexo auditivo de sobressalto - Silva, André Valério da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The acoustic startle reflex (ASR) is a rapid motor reaction elicited by a sudden intense acoustic stimulus. This is an acoustic-motor reflex of brainstem conserved across mammal's species including man. Moreover the ASR is defensive behavior against both possible ag-gressive and alert to unexpected events. The ASR evokes responses of skeletal muscles as well as of autonomic nervous system with elevation of blood pressure and acceleration of the heart rate. In the rat, the elementary neural circuitry of ASR is mediated by ganglion cells of the organ of Corti, the cochlear root neurons (CRN), the pontine caudal reticular nucleus (PnC) and motoneurons of the spinal cord. The ASR could be modulated by habituation, sensitization, prepulse inhibition (PPI), and fear potentiation. These modulations were medi-ated by the influence of neuroactive substances on components of neuronal circuitry of ASR. In this work we evaluate the origin of monoaminergic (serotonin and noradrenaline) and CART-ergic afferents to CRN and PnC. Adult Female Wistar rats (n=54) were submitted to injections of retrograde and anterograde neuronal tracers in track-tracing experiments and identification of neuroactive substances in brain by immunohistochemistry technique. All ex-perimental protocols are according with Ethics Committee on Animal Use (protocol: 17/08). Our results demonstrate that noradrenergic area A5 (A5) is a source of noradrenergic and CART-ergic afferents to CRN and PnC, and dorsal raphe nucleus (DR) is origin of seroto-ninergic afferents to these regions. There are reciprocal connections between DR, A5 and PnC. Furthermore, after 14 and 21 days of lesion in A5, the percentage of PPI increased during intervals of 100 and 150 milliseconds without modification of ASR. This data suggest that A5 have direct action on elementary circuit of ASR evidenced his connections and modulation of PPI. Moreover, A5 and DR connections bring new insights about modulation ...

O reflexo auditivo de sobressalto (RAS) é uma reação motora rápida e evidente frente a um estímulo acústico intenso e inesperado. Trata-se de um reflexo acústico-motor do tronco encefálico que está presente em muitas espécies de mamíferos, incluindo o homem. Possui caráter tanto defensivo frente a uma possível agressão quanto de alerta frente a aconteci-mentos não esperados. Além do RAS resultar em uma resposta sobre a musculatura esque-lética, possui ação sobre o sistema nervoso autônomo promovendo aumento da pressão arterial e da freqüência cardíaca. No rato o circuito neural elementar do RAS é constituído por: neurônios do gânglio espiral, neurônios da raiz coclear (CRN), neurônios reticuloespi-nais do núcleo reticular caudal da ponte (PnC) e motoneurônios da medula espinal. O RAS pode ser modulado pela habituação, sensibilização, inibição por estímulo prévio (PPI) e pela potenciação por um estímulo adverso. Estas modulações podem ocorrer mediante a influên-cia de diversas substâncias neuroativas sobre os componentes deste circuito. Neste traba-lho avaliamos a origem de aferências monoaminérgicas (serotonina e noradrenalina) e CART-érgicas para os CRN e PnC. Para isso foram utilizados 54 ratos Wistar, adultos fê-meas, que foram submetidos a injeções de traçadores neuronais anterógrados e retrógrados para mapeamento de vias nervosas e a identificação imuno-histoquímica de substâncias neuroativas. Todos os protocolos experimentais foram aprovados pela Comissão de Ética no Uso de Animais do Instituto de Biociências de Botucatu - UNESP (protocolo no 17/08). Nos-sos resultados demonstram que o grupamento noradrenérgico A5 é uma fonte de aferências noradrenérgicas e CART-érgicas para os CRN e PnC, enquanto que o núcleo dorsal da rafe (DR) é a origem de aferências serotoninérgicas para estas regiões. Existem conexões recí-procas entre o DR, o A5 e o PnC. Além disso,...
Source of monoaminergic and CART-ergic afferets to the elementary circuitry of the acoustic startle reflex
Keywords: Reflex, Startle; Serotonina; Norepinefrina; Neurorreguladores; Reflexo de sobressalto; Reflexos; Circuitos neurais